Speaking Anxiety in a Foreign Language Speaking Class: the Perspectives of Students’ and a Teacher - Nababan, Elnora May; Lestariningsih, Fransisca Endang (FKIP Universitas Lampung, 2024)
Abstract: Speaking Anxiety in A Foreign Language Speaking Class: The Perspectives of Students’ And A Teacher. Objectives: This study aimed at investigating students’ speaking anxiety in a foreign language speaking class, the source of the anxiety, and the strategies to reduce their anxiety, in the perspectives of the students, themselves, and the teacher. Methods: Observation and interviews were applied in this qualitative study. The observation was conducted to choose six students as the interviewees with three categories according to students’ levels of speaking ability; high, medium, and low. The chosen students and the teacher of the speaking class were, then, interviewed to answer the research questions. Findings: The interview showed that students still experienced anxiety even though they had learned English since elementary school and had joined extra English courses or competitions. Additionally, students felt anxious due to huge gap between learning at school and in university levels. Related to the cause of students’ speaking anxiety, it was from the internal factor, like shyness, fear of being laughed, or lack of confidence. Peer pressure from friends who were likely more fluent was another factor influencing students' speaking anxiety. Conclusion: The strategies to reduce students’ speaking anxiety from their view were by practicing and motivating themselves. From the teacher's perspective, the best strategy to lessen speaking anxiety were providing counselling session and used Flipgrid, a platform, to collect speaking video tasks. In addition, this study could help teachers in dealing with students’ speaking anxiety, particularly in the pandemic era. Keywords: speaking anxiety, foreign language speaking class, students’ views, teacher’s view.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202414